Therapy of Human Chorionic Gonadotropin (hCG) Hormone in Dairy Cattles that Have Repeat Breeder on Pregnancy Rate in Tulungagung, East Java, Indonesia - Muhammad Aulia Rahman; Sri Pantja Madyawati; Oky Setyo Widodo; Pudji Srianto; Trilas Sardjito; Rimayanti (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study aimed to prove that giving hCG injection at the time of artificial insemination and five days afterartificial insemination in dairy cows with repeat breeder can cause pregnancy. This study employed 30 dairycows with repeat breeder. All samples of dairy cows were divided into two treatments, P1 using hCG at adose of 100 IU given intramuscularly at the time of artificial insemination and P2 using hCG at a dose of100 IU intramuscularly given five days after artificial insemination. The results were analyzed using the Chi-Square test. Analysis using Chi-Square showed that all treatments caused pregnancy (100%). In summary,hCG injection at the time of artificial insemination and five days after artificial insemination in dairy cowsexperiencing repeat breeding can cause pregnancy.